2001
DOI: 10.1073/pnas.98.3.1142
|View full text |Cite
|
Sign up to set email alerts
|

Genetic remodeling of protein glycosylation in vivo induces autoimmune disease

Abstract: Autoimmune diseases are among the most prevalent of afflictions, yet the genetic factors responsible are largely undefined. Protein glycosylation in the Golgi apparatus produces structural variation at the cell surface and contributes to immune self-recognition. Altered protein glycosylation and antibodies that recognize endogenous glycans have been associated with various autoimmune syndromes, with the possibility that such abnormalities may reflect genetic defects in glycan formation. We show that mutation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
122
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(131 citation statements)
references
References 35 publications
7
122
0
Order By: Relevance
“…In support of this proposition are findings of hyposialated CD45RA in B cell lymphomas and activated human cells (42). Interestingly, a recent study has shown that a mutation in the gene encoding ␣-mannosidase II, an enzyme involved in the branching of asparagine N-linked oligosaccharide chains (N-glycans), resulted in lupus-like disease in mice (43).…”
Section: Discussionmentioning
confidence: 88%
“…In support of this proposition are findings of hyposialated CD45RA in B cell lymphomas and activated human cells (42). Interestingly, a recent study has shown that a mutation in the gene encoding ␣-mannosidase II, an enzyme involved in the branching of asparagine N-linked oligosaccharide chains (N-glycans), resulted in lupus-like disease in mice (43).…”
Section: Discussionmentioning
confidence: 88%
“…Inactivation of ␣-mannosidase II (22,23,25), and ␣-mannosidase IIx (24,25) individually reduces overall complex N-glycan synthesis significantly, but the mice are viable, albeit with different consequences, causing anemia or male infertility, respectively. However, ablation of both genes completely abrogates complex N-glycan formation with the accumulation of hybrid structures (25,38).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the unique cell-and tissuespecific roles of individual members of multigene enzyme families have also been revealed by these studies. For example, ␣-mannosidase II-deficient mice develop dyserythropoietic anemia and autoimmune disease (22,23), yet disruption of the mouse ␣-mannosidase IIx gene results in hypospermatogenesis and male infertility (24). However, ablation of both ␣-mannosidase II and IIx completely abrogates complex N-glycan biosynthesis with the accumulation of hybrid structures, and causes hepatic and pulmonary ultrastructural defects.…”
mentioning
confidence: 99%
“…Con A reactivity of nM60s, indicative of high mannose, reproduces a feature of the native glycoprotein (35) that has been exploited in affinity purification (5) and for characterization of megalin in rat kidney (30). Various post-translational modifications, and glycosylation in particular, can introduce or mask immunoreactive determinants that can be associated with pathogenic autoimmune responses (36,37). The specific attribution of such a determinant to this model of pathogenic autoimmunity could lead to additional insight into the mechanism of disease progression.…”
Section: Discussionmentioning
confidence: 99%